Preliminary Design of Tertiary Butyl Alcohol Plant from Isobutylene and Water, Capacity of 80,000 Tons/Year - Ratnasari, Desi; , Ir. Herry Purnama, M.T., Ph.D; , Tri Widayatno,S.T., MS.c., Ph.D (2016)
The Tertiary Butyl Alcohol (TBA) plant has a capacity of 80,000 tons per year. The plant is planned to operate for 330 days per year. TBA making process is carried out in a bubble reactor liquid-gas phase, non-adiabatic and isothermal. The process takes place at a temperature of 70°C and a pressure of 1.4 atm in irreversible and exothermic reaction. This plant is classified low risk plant. Each year, the need for raw materials isobutylene is 58,192.4872 tons and water is 21,880.5938 tons. Process supporting units (Utilities) consist of cooling water, sanitary water, boiler feed water, process water, steam, electricity, fuel, and compressed air. Total water needed is about 88,384.4799 kg/hour supplied from Cimanuk River. Steam supply is about 9,388.1468 kg/hour then obtained from the boiler. The fuel for boiler is used fuel oil as much as 1.4710 m3/hour. Compressed air needs is about 50 m3/hr. Electricity is supplied by State Electricity Company (PLN) as much as 321.62 kW and generator for backup power is about 550 kW by using diesel fuel of 1.76 m3/hr. The plant was established in the industrial area of Indramayu, West Java. Total land area is 27,030 m2. Isobutylene raw material is obtained from UP VI Balongan, Indramayu, West Java. The number of employees are 125 people. TBA plant needs 480,322,499,166.48 IDR of fixed capital and 145,074,950,600.34 IDR of working capital. Based on the economic analysis, the plant will get 271,474,519,769.99 IDR of profit before tax. The plant will get 190,032,163,838.99 IDR of profit after 30% of tax per year. Number of percent Return of Investment (ROI) before tax and after tax is 56.52% and 39.56% respectively. Pay Out Time (POT) before tax and after tax is about 1.5 years and 2 years. Break Even Point (BEP) is 42.92% and shut down point is 28.46%. Internal Rate of Return (IRR) is 33%. Based on the economic feasibility, it is concluded that the TBA plant is feasible to be built.